Elevated White Blood Cell Count Does Not Predict Clostridium difficile Nucleic Acid Testing Results. (10th February 2021) - Bosch, Dustin E; Mathias, Patrick C; Krumm, Niklas; Bryan, Andrew; Fang, Ferric C; Greninger, Alex L
Abstract: Background: An elevated white blood cell count (WBC; >15 000/μL) is an established prognostic marker in patients with Clostridium difficile infection (CDI). Small observational studies have suggested that a markedly elevated WBC should prompt consideration of CDI. However, there is limited evidence correlating WBC elevation with the results of C. difficile nucleic acid amplification testing (NAAT). Methods: Retrospective review of laboratory testing, outcomes, and treatment of 16 568 consecutive patients presenting to 4 hospitals over 4 years with NAAT and WBC testing on the same day. Results: No significant relationship between C. difficile NAAT results and concurrent WBC in the inpatient setting was observed. Although an elevated WBC did predict NAAT results in the outpatient and emergency department populations ( P < .001), accuracy was poor, with receiver-operator areas under the curve of 0.59 and 0.56, respectively. An elevated WBC (>15 000/μL) in CDI was associated with a longer median hospital length of stay (15.5 vs 11.0 days; P < .01), consistent with leukocytosis as a prognostic marker in CDI. NAAT-positive inpatients with elevated WBC were more likely to be treated with metronidazole and/or vancomycin (relative ratio, 1.2; 95% confidence interval [CI], 1.1–1.3) and die in the hospital (relative ratio, 2.9; 95% CI, 2.0–4.3). Conclusions: Although WBC is an important prognostic indicator in patients with CDI, an isolated WBC elevation has low sensitivity and specificity as a predictor of fecal C. difficile NAAT positivity in the inpatient setting. A high or rising WBC in isolation is not a sufficient indication for CDI testing. Abstract : White blood cell count (WBC) may predict hospital length of stay and in-hospital mortality for patients undergoing Clostridium difficile NAAT. However, WBC is a poor predictor of NAAT results. Elevated or rising WBC is not a sufficient indication for CDI testing.